SEX , STORAGE AND SYMBIONTS: OPTIMIZING MACROCYSTIS PYRIFERA GERMPLASM FOR KELP AQUACULTURE - (:unkn) unknown (My University, 2025)
As climate change and anthropogenic stressors accelerate the degradation of marine ecosystems, the need for resilient, reproductively competent germplasm to support seaweed aquaculture and restoration has never been more urgent. Yet, the evolutionary and biological integrity of long-term stored germplasm remains poorly understood. This dissertationinvestigates how artificial storage conditions reshape gene expression, host–microbe dynamics, and reproductive capacity in Macrocystis pyrifera, a foundational kelp species critical to temperate marine ecosystems and emerging aquaculture industries. By integrating transcriptomics, microbial community profiling, and fertility assessments, this work examines how ex situ conservation affects the viability and function of preserved gametophyte cultures. In Chapter 1, we examine how sex and light interact to regulate reproductive gene expression in male and female M. pyrifera gametophytes. Using RNA-seq, we identified large-scale sex-biased transcriptional programs that are differentially activated by red and blue light. Males exhibited nearly twice the number of over-expressed genes compared to females under both light treatments, particularly those related to cytoskeletal remodeling, motility, and signal transduction. In contrast, females over-expressed genes involved in metabolic processes, photosynthesis, and structural organization. We also identified over 1,000 genes with significant sex-by-light interaction effects, suggesting that environmental cues modulate gene expression in a context-dependent manner. These patterns underscore the importance of light as a developmental signal in gametogenesis and highlight the potential risks of disrupting sex-specific regulatory programs in hatchery or conservation settings where light regimes are manipulated. Chapter 2 focuses on microbial succession and host-microbiome interactions across long-term storage and recovery phases. Through 16S rRNA sequencing, we demonstrate that microbial communities undergo significant shifts during storage, characterized by a decrease in richness and compositional changes that reflect both ecological succession and storage-induced dysbiosis. Dysbiosis emerged in some cultures and correlated with reduced fertility, particularly at later recovery stages. Indicator species analysis identified taxa such as Pseudomonas as being associated with lower fertility, while others, like Nitratireductor and Labrenzia, were linked to higher reproductive success. Although antibiotic treatments altered microbial composition, reducing diversity and shifting community profiles, they did not consistently improve fertility outcomes. These results suggest that microbial community structure alone is not a reliable predictor of host performance, highlighting the complexity of host–microbiome interactions in cultured kelp gametophytes and the need for more targeted approaches to manipulate the microbiome in support of germplasm viability. In Chapter 3, we assess how reproductive performance changes over time in stored cultures, quantifying gametophyte fecundity and fertility as a function of storage duration and recovery conditions. Fecundity, measured by the number of live eggs, attached or detached, and fertility, measured by the number of sporophytes and embryos. We observed a general decline in reproduction with prolonged storage; however, gametophytes given longer recovery periods (GL treatment) frequently regained reproductive capacity comparable to or exceeding that of short-term recovered individuals (GS treatment). Notably, newly isolated gametophytes with no prior storage (NG treatment) exhibited the lowest fecundity and fertility, a surprising outcome that suggests gametophytes may require acclimation or developmental reprogramming to optimize reproductive success under lab conditions. This finding also points to possible effects of seasonal plasticity or age-related readiness, as NG cultures were collected outside the peak reproductive window. On average, GL cultures exhibited the highest number of sporophytes per frame, followed by GS, with NG cultures performing significantly worse across genotypes. Female and male genotypes had high variability among individuals, and genotype-specific patterns were evident within each treatment, emphasizing that reproductive potential is both genetically and environmentally regulated. Our results demonstrate that while long-term storage (LTS) can negatively impact gametophyte fertility, these effects can be mitigated by allowing sufficient recovery time. Moreover, the poor performance of wild-collected gametophytes highlights the importance of both developmental context and controlled acclimation in ex situ conservation programs. Together, these findings reveal that reproductive viability in kelp germplasm is not simply preserved by survival. It is shaped by evolving transcriptional landscapes, shifting microbial assemblages, and time-dependent physiological recovery. This dissertation emphasizes the need for conservation practices that maintain evolutionary functionality, not just genetic material. Recommendations include incorporating genotype-specific light regimes, microbial monitoring, and structured recovery protocols into kelp hatchery design. By addressing the biological complexity of stored gametophytes, this work lays a foundation for more reliable and informed germplasm management in seaweed aquaculture and restoration.
Keywords: Molecular biology; Botany; fertility; gametophyte; Gene expression; Germplasm; Longevity; Microbiome